Inconsistencies & Problems of Supreme Court Decision No. 26 B/Pdt.Sus-Arbt/2014 concerning Annulment of Arbitration Award - Zakaria, Zurisman; Sudirman, Sudirman; Umar, Wahyudi (Faculty of Law, Universitas Pekalongan, 2024)
Arbitration awards are usually considered an efficient and effective way to resolve business disputes. However, just like an award in a court, an arbitral award may also be annulled if it meets the requirements mentioned in Article 70 of the Arbitration Law. This study aims to analyze the inconsistencies of the Supreme Court decision No. 26/Pdt.Sus-Arbt/2014 which annulled the arbitral award. This research uses normative legal research methods by applying a statutory law approach and a case approach. Based on the results of the study, there are inconsistencies in the Supreme Court decision No. 26/Pdt.Sus-Arbt/2014 which annulled the BANI arbitration award No. 442/I/ARB-BANI/2012 by considering factors outside the contents of article 70 of the Arbitration Law. Observing this phenomenon, it is important to add articles that provide guidance on the use of reasons outside the contents of article 70 of Law No. 30 of 1999 in the annulment of arbitral awards, with the aim of providing legal certainty.